Interlaboratory comparisons on determining of alcohol by volume (abv) in vodka Measurement standards - L. I. Goryaeva; E. K. Fatkulina; E. P. Shchukina (Стандартные образцы)
The article provides an analysis of accuracy indicators for measuring the alcohol by volume (ABV) in vodka performed by various methods according to GOST 32035–2013 «Vodka and Special Vodka. Acceptance Rules and Methods of Anlysis». The results of two rounds of the interlaboratory comparisons on determination of the ABV in vodka conducted to verify the qualifications of accredited testing laboratories are described.Information is provided on the development of the GSO 11142–2018 reference material for the volume fraction of ethanol in an aqueous solution (VER-2), certified for the volume fraction of ethanol in an aqueous solution, instances of which were used during the interlaboratory comparisons. The conclusion is made about the satisfactory quality of measurements of ABV in vodka in the accredited laboratories.